Optical laminate, method for manufacturing same, smart window comprising same, and window for automobile or

By using an optical laminate containing a liquid crystal layer and a conductive polymer material on the glass window, the problem of fixed transmittance of traditional glass windows is solved, and the line of sight adaptability in the case of sufficient and insufficient light is achieved, the risk of reflection and cracks is reduced, and infrared barrier and energy efficiency are improved.

CN120569665APending Publication Date: 2025-08-29DONGWOO FINE CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380091441.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-17
Filing Date
2023-10-26
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

In the prior art, the glass window transmittance of traditional mobile tools is fixed, resulting in the problem of poor driver vision in the case of sufficient light and insufficient light, and problems of reflection, cracks and high costs.

Method used

An optical laminated body including a liquid crystal layer and two optical functional layers is adopted. Each layer includes a base material layer and a functional conductive layer. The conductive polymer material is used to optimize the laminated structure to reduce reflection and improve infrared barrier rate, and avoid cracks and surface resistance caused by external stress.

Benefits of technology

It is achieved to reduce the solar light transmittance while increasing infrared barrier rate, reduce cracks and surface resistance increase, simplify manufacturing processes, and improve energy economy and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120569665A_ABST
    Figure CN120569665A_ABST
Patent Text Reader

Abstract

The present invention relates to an optical laminate comprising: a liquid crystal layer; a first optical functional layer formed on one surface of the liquid crystal layer; and a second optical functional layer formed on the other surface of the liquid crystal layer and facing the first optical functional layer, the first optical functional layer and the second optical functional layer each independently including a base material layer and a functional conductive layer, at least one of the first optical functional layer and the second optical functional layer includes two or more functional conductive layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical laminate and a method for producing the same, a smart window including the same, and a window for an automobile or a building to which the same is applied. Background Art

[0002] Generally speaking, glass windows of vehicles and other mobile vehicles are often coated with external light blocking coatings. However, the transmittance of glass windows of conventional mobile vehicles is fixed, and the transmittance of external light blocking coatings is also fixed. Therefore, since the overall transmittance of the windows of such conventional mobile vehicles is fixed, accidents may occur. For example, if the overall transmittance is set low, there will be no problem during the day when the surrounding light is sufficient. However, in situations such as at night when the surrounding light is insufficient, there is a problem that it is difficult for the driver and the like to correctly see the surroundings of the mobile vehicle. In addition, if the overall transmittance is set high, there is a problem that it may cause glare to the driver and the like during the day when the surrounding light is sufficient. For this reason, an optical laminate has been developed that can change the transmittance of light when a voltage is applied.

[0003] The optical laminate is driven by applying voltage to drive the liquid crystal, thereby changing the transmittance. Optical laminates developed so far are produced by forming a conductive layer for driving the liquid crystal on a separate substrate and then combining it with other elements such as a polarizing plate.

[0004] For example, Japanese Patent Publication No. 2018-010035 also discloses an optical laminate comprising a functional electrode layer formed on a polycarbonate (PC) substrate having a predetermined thickness. However, in the case where a separate substrate is included to form a conductive layer, there are problems such as the production process becoming complicated and the manufacturing cost increasing, the thickness of the laminate becoming thicker, and the transmittance changing due to the phase difference. In addition, indium tin oxide (ITO), the electrode material mainly used for the above-mentioned functional electrode layer, is an inorganic oxide. Even if the external stress changes slightly, it is easy to crack (crack), and the surface resistance increases, which is not conducive to the production of optical laminates in various forms.

[0005] Korean Patent Publication No. 10-2265762 discloses an infrared-blocking electrode adhesive and a smart window containing the same. These adhesives combine infrared-blocking and electrode functions into a single adhesive layer, creating a single coating for ease of use and cost reduction. The infrared-blocking electrode adhesive contains metal nanowires. However, using metal or metal alloys in the functional layer applied to the window can lead to glare, resulting in poor appearance and the risk of accidents. Furthermore, the window's durability may be affected by cracks caused by external impact.

[0006] Therefore, there is a real need to develop a high-quality optical laminate having low reflection and heat shielding properties and high durability. Summary of the Invention

[0007] Technical issues

[0008] In order to solve the above-described problems, an object of the present invention is to provide an optical laminate that can reduce the transmittance of solar light while increasing the infrared ray blocking rate to save energy.

[0009] Another object of the present invention is to provide an optical layered body capable of preventing the generation of cracks due to external stress and reducing the rate of increase in surface resistance.

[0010] Another object of the present invention is to provide a smart window comprising the optical layered body and a window for an automobile or a building to which the smart window is applied.

[0011] However, the problems to be solved by the present invention are not limited to the problems mentioned above, and those skilled in the art should be able to clearly understand other problems not mentioned based on the following description.

[0012] Solutions to Problems

[0013] The present invention relates to an optical laminate, which comprises: a liquid crystal layer; a first optically functional layer formed on one side of the liquid crystal layer; and a second optically functional layer formed on the other side of the liquid crystal layer and opposite to the first optically functional layer, wherein the first optically functional layer and the second optically functional layer each independently comprise a substrate layer and a functional conductive layer, and at least one of the first optically functional layer and the second optically functional layer comprises two or more layers of the functional conductive layer.

[0014] The present invention may be characterized in that the functional conductive layer comprises a conductive polymer.

[0015] In the present invention, the conductive polymer may include a material selected from the group consisting of polythiophene, poly(3,4-ethylenedioxythiophene), polyaniline, polyacetylene, polydiacetylene, polyphenylene, polyphenylenevinylene, polyphenylene sulfide, polythienylene vinylene, polythiophene ... One or more selected from the group consisting of polyvinylene, polyfluorene, polypyrrole, poly(3,4-ethylenedioxythiophene), poly(3,4-ethylenedioxythiophene):polystyrenesulfonate, poly(3,4-ethylenedioxythiophene):camphorsulfonic acid, poly(3,4-ethylenedioxythiophene):toluenesulfonic acid, poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid, polyaniline:polystyrenesulfonate, polyaniline:camphorsulfonic acid, polypyrrole:polystyrenesulfonate, polypyrrole:camphorsulfonic acid, polypyrrole:toluenesulfonic acid, polypyrrole:dodecylbenzenesulfonic acid, polythiophene:polystyrenesulfonate, polythiophene:camphorsulfonic acid, polythiophene:toluenesulfonic acid, and polythiophene:dodecylbenzenesulfonic acid.

[0016] In the present invention, the thickness of the functional conductive layer may be 1.0 to 3.0 μm.

[0017] In the present invention, the base layer may include one or more selected from the group consisting of cycloolefin resins, cellulose resins, acrylic resins, polyester resins, and polycarbonate resins.

[0018] In the present invention, the base layer may include a polarizer.

[0019] The present invention may be characterized in that the liquid crystal layer is polarizing film-liquid crystals (POL-LC) or polymer dispersed liquid crystals (PDLC).

[0020] In the present invention, the optical layered body may have a solar energy blocking rate of 60% or more as measured according to the optical performance test method KS L 2016:2014, 6.3.

[0021] In the present invention, at a tensile deformation rate of greater than 1% and less than 10%, at least one of the crack density values ​​of the functional conductive layer calculated according to the following formula 1 may be 0 to 0.05.

[0022] [Formula 1]

[0023] ρ(ε)=l(ε) / A

[0024] (In the above formula 1, ε represents the tensile deformation rate (%), and A represents the area of ​​the observation area (mm 2 ), the above ρ(ε) represents the crack density value of the functional conductive layer calculated under the tensile deformation rate ε, and the above l(ε) represents the crack area (mm) of the functional conductive layer in the observation area A measured under the tensile deformation rate ε 2 ). )

[0025] In the present invention, when ε in the above formula 1 is 2%, the crack density of the above functional conductive layer calculated according to the above formula 1 may be 0.

[0026] In the present invention, at a tensile deformation rate of 1% to 10%, at least one of the increase rates of the surface resistance of the functional conductive layer calculated according to the following formula 2 may be 15% or less.

[0027] [Formula 2]

[0028] δ(ε)=[{RS(ε) / RS(0)}-1]*100

[0029] (In the above formula 2, the above δ(ε) represents the increase rate (%) of the sheet resistance of the functional conductive layer calculated at the tensile deformation rate ε, the above RS(ε) represents the sheet resistance value (Ω / □) of the functional conductive layer measured at the tensile deformation rate ε, the above RS(0) represents the sheet resistance value (Ω / □) of the functional conductive layer measured in the initial state with a tensile deformation rate of 0%, and the above ε has the same meaning as in formula 1.)

[0030] In the present invention, at a tensile deformation rate of 1% to 10%, at least one of the increase rates of the surface resistance of the functional conductive layer calculated according to Formula 2 may be 14% or less.

[0031] In the present invention, the functional conductive layer and the base layer may be formed in direct contact without involving a separate base material.

[0032] In the present invention, the functional conductive layer and the base layer may be formed in direct contact with each other with an easy-adhesion layer interposed therebetween.

[0033] In the present invention, the liquid crystal layer may include at least one selected from the group consisting of ball spacers and column spacers.

[0034] In the present invention, the optical layered body may further include one or more selected from the group consisting of a protective film, an oriented film, a tacky / adhesive layer, a UV absorbing layer, and a hard coat layer.

[0035] Furthermore, the present invention aims to provide a method for producing the above-mentioned optical layered body.

[0036] The present invention also aims to provide a smart window including the optical laminate, and windows for automobiles and buildings to which the smart window is applied.

[0037] Effects of the Invention

[0038] According to the optical layered body of the present invention, since the transmittance of solar light is reduced and the infrared ray blocking rate is increased, energy efficiency can be improved.

[0039] Furthermore, according to the optical layered body of the present invention, the generation of cracks due to external stress and the rate of increase in surface resistance can be further reduced compared to conventional transparent electrode films.

[0040] Furthermore, according to the optical laminate of the present invention, since the functional conductive layer and the substrate layer are in direct contact without a separate layer, a step for bonding the substrates can be omitted, and the production process can be simplified compared to conventional methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a diagram showing the stacked structure of an optical stack according to one embodiment of the present invention.

[0042] Figure 2 This is a diagram showing the stacked structure of optically functional layers in the optical layered body according to one embodiment of the present invention.

[0043] Figure 3 This is a diagram showing a stacked structure in which a polarizing plate is used as an optical functional layer in an optical stack according to another embodiment of the present invention.

[0044] Figure 4 This is a diagram showing a laminated structure in which a polarizing plate is used as an optical functional layer in an optical laminate according to still another embodiment of the present invention.

[0045] Figure 5 1 is a diagram illustrating a laminate structure of a vehicle smart window to which an optical laminate is applied according to an embodiment of the present invention.

[0046] Figure 6 1 is a diagram showing a stacked structure of a smart window for architectural use using an optical stack according to another embodiment of the present invention.

[0047] The meanings of the reference numerals in the above drawings are as follows.

[0048] 100: Optical laminate

[0049] 110: Optical functional layer

[0050] 120: Liquid crystal layer

[0051] 130: Adhesive / adhesive layer

[0052] 140: Glass

[0053] 141: Vehicle glass

[0054] 142: Architectural window glass

[0055] 210: Functional conductive layer

[0056] 220: base material layer

[0057] 300: Polarizing plate

[0058] 310: Polarizer

[0059] 320: Protective film DETAILED DESCRIPTION

[0060] The present invention relates to an optical laminate which reduces the transmittance of solar rays, improves the infrared ray blocking rate, and reduces the generation of cracks and the increase rate of surface resistance caused by external stress.

[0061] In more detail, it relates to an optical laminate, which includes: a liquid crystal layer; a first optically functional layer formed on one side of the liquid crystal layer; and a second optically functional layer formed on the other side of the liquid crystal layer and opposite to the first optically functional layer, the first optically functional layer and the second optically functional layer each independently include a substrate layer and a functional conductive layer, at least one of the first optically functional layer and the second optically functional layer includes two or more layers of the functional conductive layer, and the functional conductive layer is characterized by including a conductive polymer.

[0062] The optical laminate of the present invention is particularly suitable for the technical field in which light transmittance can be changed by application of voltage, and can be used, for example, in smart windows and the like.

[0063] A smart window is an optical structure that changes its light transmittance in response to an electrical signal, thereby controlling the amount of light or heat that passes through it. Specifically, a smart window can change state to transparent, opaque, or translucent depending on the voltage applied. It is also known as variable-transmittance glass, dimming glass, or smart glass.

[0064] Smart windows can be used as partitions for dividing the interior space of vehicles and buildings or for protecting privacy, or as skylights arranged in openings of buildings. They can also be used as highway signs, billboards, scoreboards, clocks or advertising screens, and can replace the glass of transportation vehicles such as windows or skylights of cars, buses, airplanes, ships or trains.

[0065] The optical laminate of the present invention can also be used as a smart window in the various technical fields described above. However, the liquid crystal laminate contained in the optical laminate has a conductive layer formed directly on the polarizing plate and does not include a separate substrate for forming the conductive layer. Therefore, the thin thickness is favorable for bending properties, and thus it can be particularly suitable for use in smart windows for vehicles or buildings. In one or more embodiments, the smart window using the optical laminate of the present invention can be used for the front window, rear window, side window, and skylight of a car, or a window for a building, etc. In addition to being used for blocking external light, it can also be used for internal space division or privacy protection purposes such as internal partitions in cars or buildings.

[0066] The following describes the embodiments of the present invention in more detail with reference to the accompanying drawings. However, the following drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and to facilitate a deeper understanding of the above-described invention and the technical concept of the present invention. Therefore, the present invention should not be interpreted solely in accordance with the matters described in these drawings.

[0067] The terms used in this specification are intended to describe the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified in the context, the singular form also includes the plural form. For example, the "functional conductive layer" used in this specification may refer to at least one of the first functional conductive layer and the second functional conductive layer. The "optical functional layer" may refer to at least one of the first optical functional layer and the second optical functional layer. The "transparent conductive layer" may refer to at least one of the first transparent conductive layer and the second transparent conductive layer.

[0068] The terms "comprises" and "comprising" used in this specification are used to mean that they do not exclude the existence or addition of one or more other constituent elements, steps, operations, and / or elements other than the mentioned constituent elements, steps, operations, and / or elements. Throughout the specification, the same reference numerals refer to the same constituent elements.

[0069] As illustrated in the accompanying drawings, spatially relative terms such as "below", "bottom", "lower", "above", "upper surface", "upper", etc. can be used to easily describe the relationship between one element or constituent element and other elements or constituent elements. Spatially relative terms should be understood as terms that include different directions of the elements when in use or in operation in addition to the directions illustrated in the drawings. For example, when the elements illustrated in the drawings are turned over, the elements described as "below" or "lower" of other elements can be placed "above" other elements. Therefore, the exemplary term "below" can include both the directions of below and above. Elements can also be oriented in other directions, so spatially relative terms can be interpreted based on the orientation.

[0070] The “top-view direction” used in this specification may be interpreted as a direction perpendicular to the polarizing plate and / or the transparent conductive layer, that is, a direction viewed from the visible side of a user.

[0071] The term “substantially” used in this specification may be interpreted not only as being physically identical or identical, but also as being within the error range of the measurement or manufacturing process. For example, the error range may be interpreted as being below 0.1%.

[0072] <Optical laminate>

[0073] Figure 1 : is a diagram showing the stacked structure of an optical stack according to one embodiment of the present invention. Figure 1 , the optical laminate of one embodiment of the present invention may include a first optical functional layer 110-1, a second optical functional layer 110-2 and a liquid crystal layer 120, and at least one of the first optical functional layer and the second optical functional layer may include two or more layers of the functional conductive layer. In addition, the optical laminate of one embodiment of the present invention may be bonded to the glass 140 using an adhesive / bonding layer 130 on both sides of the optical laminate including the liquid crystal layer 120 and the optical functional layer 110. More specifically, at least one of the first optical functional layer 110-1 and the second optical functional layer 110-2 may be provided with a functional conductive layer 210 on both sides of the substrate layer (refer to Figure 2 、 3 ), as will be described later, the substrate layer is a concept including a polarizer or a polarizing plate. In addition, a functional conductive layer may be provided on the outer side and the inner side of the substrate layer. For example, at least one of the first optically functional layer and the second optically functional layer may include two layers of the functional conductive layer, and one layer may be provided on the outer side of the substrate layer (more specifically, the polarizing plate 300), and the other layer may be provided between the polarizer 310 and the protective film 320, that is, inside the substrate layer (more specifically, the polarizing plate 300) (refer to Figure 4). Regarding the functional conductive layer 210, when two or more layers are provided in one optical functional layer, compared to when a single layer is provided, the reflectivity of visible light can be reduced (low reflection characteristics) and the solar energy blocking rate is excellent (heat insulation characteristics). Therefore, the optical layered body of the present invention has the characteristic of improving energy economy. From this aspect, it is preferably provided with 2 to 3 layers, and more preferably provided with 2 layers. Figure 1 In the figure, the layer formed on the upper surface of the liquid crystal layer is called the first optical functional layer 110-1, and the layer formed on the lower surface of the liquid crystal layer is called the second optical functional layer 110-2. However, this is for the purpose of spatially illustrating the situation where optical functional layers are formed on both sides, and may have different interpretations when facing other directions.

[0074] In one embodiment, at a tensile deformation rate greater than 1% and less than 10%, the crack density of the functional conductive layer 210 calculated according to the following formula 1 may be 0 to 0.05.

[0075] [Formula 1]

[0076] ρ(ε)=l(ε) / A

[0077] In the above formula 1, ε represents the tensile deformation rate (%), and A represents the area of ​​the observation area (mm 2 ), the above ρ(ε) represents the crack density value of the functional conductive layer calculated under the tensile deformation rate ε, and the above l(ε) represents the crack area (mm) of the functional conductive layer in the observation area A measured under the tensile deformation rate ε 2 ).

[0078] Specifically, A can refer to the area of ​​an observation region arbitrarily specified by the user for calculating the crack density of the functional conductive layer due to tensile deformation. l(ε) can refer to the area (30.36%) of the black portion of a shadow image obtained by converting an image of the functional conductive layer in the observation region taken with an optical microscope (OM) or a scanning electron microscope (SEM) into a shadow image using an image processing program such as Image J (developed by NIH / LOCI).

[0079] Therefore, the crack density value calculated according to the above formula 1 can be understood as follows: the closer it is to 0, the less likely cracks will appear in the functional conductive layer; the closer it is to 1, the more likely cracks will appear on the entire surface of the functional conductive layer.

[0080] That is, if the crack density of the functional conductive layer 210 calculated according to Formula 1 satisfies the above range at a tensile strain rate greater than 1% and less than 10%, cracks caused by changes in external stress can be prevented, thereby providing an advantage in stable driving even in the face of external stress changes. According to another embodiment of the present invention, when ε in Formula 1 is 2%, the crack density calculated according to Formula 1 is 0, achieving durability that prevents cracking even under external mechanical stimulation.

[0081] In another embodiment, at a tensile deformation rate of 1% to 10%, the sheet resistance increase rate of the functional conductive layer 210 calculated according to the following formula 2 may be 15% or less, preferably 0% to 14%.

[0082] [Formula 2]

[0083] δ(ε)=[{RS(ε) / RS(0)}-1]*100

[0084] In the above formula 2, the above δ(ε) represents the surface resistance increase rate (%) of the functional conductive layer calculated under the tensile deformation rate ε, the above RS(ε) represents the surface resistance value (Ω / □) of the functional conductive layer measured under the tensile deformation rate ε, the above RS(0) represents the surface resistance value (Ω / □) of the functional conductive layer measured in the initial state with the tensile deformation rate of 0%, and the above ε has the same meaning as in formula 1.

[0085] If the surface resistance increase rate of the functional conductive layer 210 calculated according to the above formula 2 satisfies the above range under a tensile deformation rate of 1% to 10%, it can prevent the surface resistance from increasing excessively due to external stress changes, and thus has an advantage in stable driving even when responding to external stress changes.

[0086] In one embodiment, the optical laminate has a solar energy blocking rate of 60% or more as measured according to the optical performance test method KS L 2016:2014,6.3, which is preferred from the perspectives of absorbing or blocking light in the infrared region of sunlight without interfering with necessary lighting, preventing reflections, and reducing energy consumption.

[0087] Optically functional layer 110

[0088] Reference Figure 2The first optically functional layer 110-1 and the second optically functional layer 110-2 can be formed relative to each other with the liquid crystal layer 120 as a reference. The optically functional layer 110 can include a substrate layer 220 and functional conductive layers 210 on both sides of the substrate layer. The optically functional layer 110 can be provided on both sides of the liquid crystal layer to impart optical properties such as infrared rejection, absorptivity, or reflectivity. More specifically, the optically functional layer 110 includes a conductive polymer such as poly(3,4-ethylenedioxythiophene) (PEDOT), which essentially functions as an electrode. Thus, the liquid crystals in the liquid crystal layer can be adjusted to an on or off state by an applied voltage. In addition, the characteristic of conductive polymers absorbing energy in the infrared region can be utilized to impart a heat-insulating function. When the optical layered structure of the present invention is made, it can block more than about 60% of infrared rays, preferably more than 70%, and can reduce the reflectivity of the visible light region to less than 10%, preferably less than 5%, by reflecting light in the visible light region, thereby having the characteristic of also imparting a low-reflection effect.

[0089] Functional conductive layer (210)

[0090] The functional conductive layer 210 can be provided to replace the conductive layer of the conventional optical laminate to realize the driving of the liquid crystal layer 120, and can be directly formed without including a separate substrate between it and the substrate layer 220. The optical laminate 100 used in the manufacture of conventional smart windows and the like is manufactured by forming a conductive layer for liquid crystal driving on one side of a substrate and laminating the other side of the substrate to a polarizing plate. However, the liquid crystal laminate of the present invention is characterized in that it does not include a separate substrate for forming a conductive layer or directly forms a conductive layer on one side of the substrate layer, thereby improving the transmittance and bending characteristics in the light transmission mode while reducing the thickness of the laminate. According to another embodiment of the present invention, the functional conductive layer 210 can be formed by directly contacting it with the substrate layer by including an easy-adhesion layer (not shown). The easy-adhesion layer can use the material described in the adhesive / adhesive layer in other components described later, but is not limited thereto.

[0091] The transmittance of the functional conductive layer 210 relative to visible light can be more than 50%, and it can preferably contain a conductive polymer. In addition, it can be manufactured from a functional conductive layer composition comprising a conductive polymer and one or more selected from the group consisting of an organic binder, an organic solvent, a silane coupling agent and a surfactant, and can also contain a balance of water according to the needs of the user. In this case, heat shielding can be adjusted by absorbing light in the infrared region of solar energy, thereby reducing energy consumption for cooling and heating and improving energy economy. In addition, even if the functional conductive layer 210 is deformed due to external stress, cracks can be prevented from occurring, thereby preventing the surface resistance from increasing excessively.

[0092] The conductive polymer may be a conductive polymer material developed in the past or in the future, and may include, for example, a material selected from the group consisting of polythiophene, poly(3,4-ethylenedioxythiophene), polyaniline, polyacetylene, polydiacetylene, polyphenylene, polyphenylene vinylene, polyphenylene sulfide, polythiophene acetylene, polythiophene vinylene, polyfluorene, polypyrrole, poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, poly(3,4-ethylenedioxythiophene):camphorsulfonic acid, poly(3,4-ethylenedioxythiophene):toluenesulfonic acid, poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid, polyaniline:polystyrenesulfonate, polyaniline:camphorsulfonic acid, polypyrrole:polystyrenesulfonate, polypyrrole: The conductive polymer may be one or more of the group consisting of camphorsulfonic acid, polypyrrole:toluenesulfonic acid, polypyrrole:dodecylbenzenesulfonic acid, polythiophene:polystyrenesulfonate, polythiophene:camphorsulfonic acid, polythiophene:toluenesulfonic acid, and polythiophene:dodecylbenzenesulfonic acid, preferably poly(3,4-ethylenedioxythiophene) [poly(3,4-ethylenedioxythiophene) (PEDOT)] or poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) [poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). PEDOT:PSS is particularly preferred due to its electron-donating effect as a conductive polymer. This property is influenced by the substituents attached to the polymer. The substituents of PEDOT:PSS have a relatively low energy band gap, and this band gap exists in the infrared region, allowing it to absorb infrared light.

[0093] The content of the conductive polymer is not particularly limited. Relative to the total weight of the functional conductive layer composition, the content may be 0.1 wt % to 5 wt %, preferably 0.2 wt % to 3 wt %.

[0094] The organic binder may comprise one or more selected from the group consisting of melamine resin, polyester resin, polyurethane resin, and polyacrylic resin. Alternatively, the organic binder may be a water-dispersible resin. In one embodiment, the organic binder may have a weight-average molecular weight of 5,000 g / mol to 30,000 g / mol, preferably 10,000 g / mol to 20,000 g / mol.

[0095] The content of the organic binder is not particularly limited and may be 1 wt % to 40 wt %, preferably 5 wt % to 35 wt %, and more preferably 8 wt % to 33 wt % relative to the total weight of the composition for forming a functional conductive layer.

[0096] The organic solvent may include an alcohol-based organic solvent, an ether-based organic solvent, and / or an amide-based organic solvent.

[0097] The alcoholic organic solvent reduces the surface tension of the composition for forming a functional conductive layer, thereby improving coating properties. In one embodiment, the alcoholic organic solvent can be an alcohol having 1 to 4 carbon atoms, such as methanol, ethanol, 2-methoxyethanol, propanol, isopropanol, or n-butanol.

[0098] The above-mentioned ether-based organic solvent can use ether-based organic solvents developed in the past or in the future, for example, propylene glycol monopropyl ether, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol-2-ethylhexyl ether, etc. can be used.

[0099] The amide organic solvent improves the conductivity of the functional conductive layer. In one embodiment, the amide organic solvent can be acetamide, N-methylacetamide, N-dimethylacetamide, N-methylpyrrolidone, etc.

[0100] The content of the organic solvent is not particularly limited and may be 10 to 80 wt %, preferably 15 to 65 wt %, and more preferably 20 to 60 wt % relative to the total weight of the conductive layer forming composition.

[0101] The silane coupling agent serves to enhance the adhesion of the composition for forming a functional conductive layer, thereby facilitating lamination of the functional conductive layer 210 on the base layer 220 . In one embodiment, the silane coupling agent may include one or more selected from the group consisting of trimethoxy silane, triethoxy silane, tetramethoxy silane and tetraethoxy silane. For example, the triethoxy silane may be 2-(3,4-epoxycyclohexyl)ethyltriethoxy silane, (3-aminopropyl)triethoxy silane, (pentafluorophenyl)triethoxy silane, (3-glycidyloxypropyl)triethoxy silane or (4-chlorophenyl)triethoxy silane. The trimethoxy silane may be (3-glycidyloxypropyl)trimethoxy silane. trimethoxysilane), (3-chloropropyl)trimethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (3-aminopropyl)trimethoxysilane, [3-(2-aminoethylamino)propyl]trimethoxysilane, (N,N-dimethylaminopropyl)trimethoxysilane, (3-bromopropyl)trimethoxysilane, or (3-iodopropyl)trimethoxysilane.

[0102] In order to improve the adhesion between the base layer 220 and the functional conductive layer 210 , the content of the silane coupling agent may be 0.05 wt % to 0.3 wt % relative to the total weight of the composition for forming a functional conductive layer.

[0103] The surfactant may be a silicone surfactant or an acetylene surfactant, and the silicone surfactant may be a modified silicone surfactant.

[0104] For example, commercially available products of the silicone-based surfactant include BYK-378 manufactured by BYK, and commercially available products of the acetylene-based surfactant include Dynol 604 manufactured by Air Products.

[0105] The content of the surfactant is not particularly limited, and may be 0.02 to 0.4 wt %, preferably 0.1 to 0.4 wt %, relative to the total weight of the composition for forming a functional conductive layer.

[0106] In one embodiment of the present invention, the functional conductive layer 210 can be formed by applying the above-mentioned composition for forming a functional conductive layer to the base layer 220 described later and then drying it in an oven at a temperature of 60 to 90° C. for 5 to 10 minutes. However, the present invention is not limited thereto and can be formed by methods commonly used in the art. For example, the functional conductive layer 210 can be formed by a coating process such as spin coating, roll coating, rod coating, dip coating, gravure coating, curtain coating, die coating, spray coating, blade coating, kneader coating, or a printing process such as screen printing, spray printing, inkjet printing, letterpress printing, gravure printing, or lithographic printing, or by an in-mold labeling (IML) injection method, a deposition process such as chemical vapor deposition (CVD), physical vapor deposition (PVD), or plasma enhanced chemical vapor deposition (PECVD), or a dry or wet plating process.

[0107] In one embodiment, the thickness of each of the functional conductive layers 210 may be 1.0 to 3.0 μm, preferably 1.5 to 3 μm. Since the functional conductive layer 210 places the substrate layer 220 in the middle and is formed on both sides thereof, the sum of the thicknesses of the functional conductive layers formed on both sides may preferably be 3 to 6 μm. In this case, the functional conductive layer 210 can ensure a predetermined transmittance, and the characteristic changes caused by external stress are not large, and a thin electrode film can be manufactured. When the thickness is higher than the above range, the adhesion between the substrates may be reduced, and due to the reduced density force inside the functional conductive layer 210, there may be disadvantages such as cracks that are easily generated due to external impact and / or external environmental conditions, which may lead to poor durability.

[0108] At this time, when a functional conductive layer is provided on one side of the substrate layer 220, there are limitations in absorbing and blocking light in the infrared region. Even if the thickness of the functional conductive layer is increased, the absorption rate and the blocking rate will not increase. Therefore, having functional conductive layers on both sides of the substrate layer 220 is effective for absorbing and blocking light in the infrared region.

[0109] Base material layer 220

[0110] The base layer 220 is the structural basis for forming the functional conductive layer 210 and is not particularly limited as long as its transmittance satisfies the above range.

[0111] According to one embodiment, the above-mentioned substrate layer 220 may preferably include one or more selected from the group consisting of cycloolefin resin, cellulose resin, acrylate resin, polyester resin and polycarbonate resin, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polymethylmethacrylate (PMMA), cyclic olefin polymer (COP), triacetyl cellulose (TAC), etc.

[0112] In one embodiment, the substrate layer 220 may have a thickness of 50 μm to 150 μm. If the transparent substrate layer 220 is less than 50 μm thick, it may not be able to properly support the functional conductive layer 210. If the thickness is greater than 150 μm, the thickness of the entire film may increase, thereby reducing the transmittance or flexibility of the transparent electrode film.

[0113] In one embodiment, in order to improve the adhesion between the functional conductive layer 210 and the substrate layer 220, a surface treatment may be applied to one or both surfaces of the substrate layer 220. The surface treatment is not particularly limited as long as it is used to improve the adhesion between the functional conductive layer 210 and the substrate layer 220. For example, a pretreatment process such as corona treatment, plasma treatment, ultraviolet irradiation, or primer treatment may be used. When the surface treatment is applied to one or both surfaces of the substrate layer 220, the adhesion between the functional conductive layer 210 and the substrate layer 220 is further improved. Even without separately including an optically clear adhesive (OCA) film, it is easy to form the functional conductive layer 210 on the transparent substrate layer 220, thereby having advantages in terms of improving transmittance, etc.

[0114] According to another embodiment of the present invention, the substrate layer 220 may include a polarizer, for example, may include a first polarizing plate having a polarizer and a second polarizing plate opposite to the first polarizing plate and also having a polarizer.

[0115] Reference Figure 3 The polarizing plate 300 includes a polarizer, and may further include functional layers such as a protective film 320, a phase difference adjustment layer (not shown), and a refractive index adjustment layer (not shown) on one or both sides of the polarizer. For example, the polarizing plate 300 may include a polarizer 310 and a protective film 320 laminated on one or both sides of the polarizer, may include a polarizer 310, a protective film 320 laminated on one side of the polarizer, and a phase difference adjustment layer laminated on the other side of the polarizer opposite to the one side, may include a polarizer 310, a protective film 320 laminated on one side of the polarizer, and a phase difference adjustment layer and a refractive index adjustment layer laminated in sequence on the other side of the polarizer opposite to the one side, may include a polarizer 310, a protective film 320 laminated on one side of the polarizer, and a protective film 320 and a phase difference adjustment layer laminated in sequence on the other side of the polarizer opposite to the one side.

[0116] The polarizer 310 may be a polarizer developed in the past or in the future, for example, a stretched polarizer or a coating polarizer may be used.

[0117] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA) resin. The polyvinyl alcohol (PVA) resin may be a polyvinyl alcohol resin obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith may also be mentioned. As the other monomers mentioned above, unsaturated carboxylic acid series, unsaturated sulfonic acid series, olefin series, vinyl ether series, acrylamide series monomers having an ammonium group, etc. may be mentioned. In addition, the polyvinyl alcohol (PVA) resin includes modified substances, for example, polyvinyl formal or polyvinyl acetal modified by aldehydes.

[0118] In one embodiment, the coating-type polarizer may be formed using a liquid crystal coating composition. In this case, the liquid crystal coating composition may include a reactive liquid crystal compound and a dichroic dye.

[0119] The reactive liquid crystal compound may be, for example, a compound containing a mesogen skeleton and one or more polymerizable functional groups. Such reactive liquid crystal compounds are widely known as reactive mesogens (RMs). These reactive liquid crystal compounds can be polymerized by light or heat to form a cured film that forms a polymer network while maintaining liquid crystal alignment.

[0120] The reactive liquid crystal compound may be a monofunctional or polyfunctional reactive liquid crystal compound. The monofunctional reactive liquid crystal compound may be a compound having one polymerizable functional group, and the polyfunctional reactive liquid crystal compound may be a compound having two or more polymerizable functional groups.

[0121] The above-mentioned dichroic dye is a component included in the liquid crystal coating composition to impart polarization characteristics, and has a property that the absorbance in the major axis direction of the molecule is different from the absorbance in the minor axis direction. The above-mentioned dichroic dye can use a dichroic dye developed in the past or in the future, for example, it can include one or more selected from the group consisting of azo dyes (azo dyes), anthraquinone dyes (anthraquinone dyes), perylene dyes (perylene dyes), merocyanine dyes (merocyanine dyes), azomethine dyes (azomethine dyes), phthaloperylene dyes (phthaloperylene dyes), indigo dyes (indigo dyes), dioxazine dyes (dioxazine dyes), polythiophene dyes (polythiophene dyes) and phenoxazine dyes (phenoxazine dyes).

[0122] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, and chloroform. Furthermore, the liquid crystal coating composition may further include a leveling agent, a polymerization initiator, and the like within a range that does not hinder the polarization properties of the coating film.

[0123] The protective film 320 is intended to protect the polarization characteristics of the polarizer from being affected by subsequent processes and the external environment, and can be implemented in the form of a protective film or the like.

[0124] The protective film 320 may be formed in direct contact with one or both surfaces of the polarizer, but is not limited thereto. For example, the protective film 320 may be used in a multilayer structure in which more than one protective film 320 is continuously laminated, and may be formed in direct contact with other functional layers. The position of the protective film 320 is not particularly limited as long as it is formed in direct contact with any other substrate of the optical laminate.

[0125] In one or more embodiments, the protective film 320 may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose (CDA), triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA), and cyclic olefin polymer (COP).

[0126] The phase difference adjustment layer (not shown) is intended to complement the optical properties of the optical laminate and can be implemented in the form of a phase difference film, etc., and phase difference films developed previously or in the future can be used. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light can be used, and these can be used alone or in combination.

[0127] The phase difference adjustment layer can be formed directly on one side of the polarizer, but is not limited thereto. For example, the phase difference adjustment layer can be formed on one side of the protective film 320 so that the polarizer, the protective film 320 and the phase difference adjustment layer are stacked in sequence.

[0128] The phase difference adjustment layer may be a stretched polymer film or a liquid crystal polymer film obtained by appropriately stretching a polymer film capable of imparting optical anisotropy.

[0129] In one embodiment, the above-mentioned polymer stretch film can use a polymer layer containing the following substances: polyolefins such as polyethylene (PE) or polypropylene (PP), cyclo olefin polymers (COP: cyclo olefin polymer) such as polynorbornene, polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resin (acryl resin), polycarbonate (PC), polyesters such as polyethylene terephthalate (PET), polyacrylate, polyvinyl alcohol (PVA) or triacetylcellulose (TAC) or other cellulose ester polymers, or copolymers of two or more monomers among the monomers forming the above-mentioned polymers, etc.

[0130] The method for obtaining the above-mentioned polymer stretch film is not particularly limited. For example, it can be obtained by stretching the above-mentioned polymer material after being shaped into a film. The above-mentioned method for being shaped into a film is not particularly limited. It can be shaped into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, tape casting, or by 2nd processing molding methods such as compression molding and vacuum forming. Wherein, extrusion molding and tape casting are preferably used. At this time, for example, an extruder equipped with a T-die, a circular die, etc. can be utilized to extrusion mold the unstretched film. In the case of obtaining a molded product by extrusion molding, it is possible to use a material in which various resin components, additives, etc. have been melt-mixed in advance, or it is possible to mold via melt-mixing during extrusion molding. In addition, it is also possible to use a solvent shared by various resin components, such as chloroform, methylene chloride, etc., after dissolving various resin components, to perform tape casting, drying, and solidification, thereby performing tape casting on the unstretched film.

[0131] For the above-mentioned polymer stretched film, the above-mentioned formed film can be uniaxially stretched along the machine flow direction (MD; Mechanical Direction, longitudinal or length direction) and uniaxially stretched along the direction perpendicular to the machine flow direction (TD; Transverse Direction, transverse or width direction). In addition, the biaxially stretched film can also be manufactured by stretching through a successive biaxial stretching method of roller stretching and tenter stretching, a simultaneous biaxial stretching method based on tenter stretching, a biaxial stretching method based on tubular stretching, etc.

[0132] The liquid crystal polymer film may include a polymerized reactive liquid crystal compound. The reactive liquid crystal compound is similar to the reactive liquid crystal compound of the coating-type polarizer.

[0133] In one or more embodiments, the thickness of the phase difference adjustment layer may be 10 μm to 100 μm in the case of a stretched polymer film, and may be 0.1 μm to 5 μm in the case of a liquid crystal polymer film.

[0134] The refractive index adjustment layer (not shown) is provided to compensate for the refractive index difference of the liquid crystal layer 120 caused by the functional conductive layer 210. It can improve visual characteristics by reducing the refractive index difference. Alternatively, the refractive index adjustment layer can be provided to correct the color caused by the functional conductive layer 210. Furthermore, if the functional conductive layer 210 is patterned, the refractive index adjustment layer can compensate for the difference in transmittance between the patterned area and the unpatterned area.

[0135] Specifically, the functional conductive layer 210 is stacked adjacent to other components (e.g., polarizers) with different refractive indices. This difference in refractive index with the adjacent layers may induce a difference in light transmittance. In particular, when the transparent conductive layer is patterned, the patterned area and the non-patterned area may appear different. Therefore, by including the refractive index adjustment layer, the refractive index can be compensated and the difference in light transmittance of the optical laminate can be reduced. In particular, when the functional conductive layer 210 is patterned, the patterned area and the non-patterned area will not appear different.

[0136] In one embodiment, the refractive index of the refractive index adjustment layer can be appropriately selected based on the materials of other adjacent components, and can preferably be 1.4 to 2.6, and more preferably 1.4 to 2.4. In this case, light loss caused by a significant refractive index difference between other components such as the polarizer and the functional conductive layer 210 can be prevented.

[0137] The above-mentioned refractive index adjustment layer is not particularly limited as long as it can prevent a significant refractive index difference between other components such as polarizers and the transparent conductive layers 231 and 232. Compounds previously or later developed for forming a refractive index adjustment layer can be used. For example, it can be formed by a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound.

[0138] In one embodiment, in addition to the above functional layers, the polarizing plate 300 may further include other functional layers to assist or enhance the characteristics of the polarizer. For example, in order to further improve the mechanical durability, an overcoat layer may also be included.

[0139] In one or more embodiments, the polarizing plate 300 may have a thickness of 100 to 200 μm, preferably 100 to 190 μm, and more preferably 120 to 150 μm. In this case, the substrate layer 220 may be manufactured with a thin thickness while maintaining the optical properties of the polarizing plate 300 .

[0140] Liquid crystal layer 120

[0141] The above-mentioned liquid crystal layer 120 can adjust the transmittance of light incident from one or more directions according to the electric field, thereby changing the driving mode of the above-mentioned optical layer. For example, it can be located in the light control area within the space provided by a sealant layer (not shown) and a spacer (not shown) arranged between the first polarizing plate and the second polarizing plate.

[0142] The liquid crystal layer 120 is not particularly limited as long as it is driven by an electric field and can control light transmittance. Liquid crystal compounds developed previously or in the future may be used. For example, the contents regarding the reactive liquid crystal compounds of the above-mentioned coating-type polarizer can be similarly applied.

[0143] The liquid crystal behavior of the liquid crystal layer 210 is not particularly limited. For example, a twisted nematic (TN) mode, a super twisted nematic (STN) mode, a vertical alignment (VA) mode, etc. can be used. Depending on the substrate used in the substrate layer 220, the liquid crystal layer 210 can selectively use a polarizing film-liquid crystal (POL-LC) or a polymer dispersed liquid crystal (PDLC) driven by a polarizing plate due to the polarizing properties of the polarizing plate. For example, when a polymer resin such as polyester resin is used to adjust transparency by applying a voltage, the PDLC mode is used for driving. When a polarizing plate is used, the driving principle of the POL-LC mode is adopted. The smart window using the above-mentioned PDLC mode and POL-LC mode can be attached with a separate film or by applying a coating to the glass to impart heat insulation and / or reduce reflection effects, but according to one embodiment of the present invention, it can be made into an integrated type without the need for a separate film, thereby ensuring the same level of heat insulation and / or reflectivity adjustment characteristics, and the production process can be simplified compared to the past.

[0144] The sealant (not shown) may contain a curable resin as a base resin. As the base resin, a UV-curable resin or a thermosetting resin known in the art for use in sealants may be used. The UV-curable resin may be a polymer of a UV-curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer. As the base resin for the sealant, for example, an acrylate resin, an epoxy resin, a urethane resin, a phenol resin or a mixture of the above resins may be used. In one embodiment, the base resin may be an acrylate resin, which may be a polymer of an acrylic monomer. The acrylic monomer may be, for example, a multifunctional acrylate. In another embodiment, the sealant may further contain a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In this specification, a monofunctional acrylate may refer to a compound having one acrylic group, and a multifunctional acrylate may refer to a compound having two or more acrylic groups. The curable resin may be cured by irradiation with ultraviolet light and / or heating. The ultraviolet irradiation conditions or heating conditions may be appropriately implemented within the scope that does not impair the purpose of the present application. The sealant may optionally further comprise an initiator, such as a photoinitiator or a thermal initiator. The sealant may be formed by methods commonly used in the art, for example, by applying the sealant to the periphery of the liquid crystal layer (i.e., the inactive region) using a sizing machine equipped with a nozzle.

[0145] The spacers (not shown) may include at least one of ball spacers and column spacers, with ball spacers being particularly preferred. There may be one or more ball spacers, each preferably having a diameter of 1 to 10 μm. Furthermore, to improve user visibility and transmittance in the light-transmitting mode when viewed from above, the area of ​​the ball spacers in the liquid crystal layer 210 is preferably 0.01 to 10% relative to the area of ​​the liquid crystal layer 210.

[0146] In one embodiment, the liquid crystal layer 120 may further include an alignment film as needed, for example, an alignment film may be formed on both sides of the liquid crystal layer 120 including the liquid crystal compound.

[0147] The alignment film (not shown) is not particularly limited as long as it is used to impart alignment to the liquid crystal compound. For example, the alignment film can be produced by applying an alignment film coating composition comprising an alignment polymer, a photopolymerization initiator, and a solvent and curing the composition. The alignment polymer is not particularly limited, and polyacrylate resins, polyamic acid resins, polyimide resins, cinnamate-containing polymers, etc. can be used, and any polymer that can exhibit alignment, previously developed or developed in the future, can be used.

[0148] Other components

[0149] The optical laminate of the present invention may further include other components within the scope of not impairing the purpose of the present invention, for example, it may further include a protective film 320, an adhesive / bonding layer 130 (see Figure 1 、 Figure 5 and Figure 6 ), and may further include an ultraviolet absorbing layer, a hard coating layer, and the like.

[0150] The protective film 320 can directly apply the content of the protective film of the substrate layer, so the description is omitted.

[0151] The above-mentioned adhesive / bonding layer 130 can be formed using an adhesive or a pressure-sensitive adhesive, and preferably has appropriate adhesive / bonding strength to prevent peeling, bubbles, etc. during handling of the optical laminate, while also having transparency and thermal stability.

[0152] The adhesive may be any adhesive that has been developed in the past or will be developed later. For example, a photocurable adhesive may be used.

[0153] The photocurable adhesive exhibits strong adhesive strength by crosslinking and curing upon exposure to active energy rays such as ultraviolet (UV) and electron beam (EB), and may be composed of reactive oligomers, reactive monomers, photopolymerization initiators, and the like.

[0154] The reactive oligomer is a key component that determines the properties of the adhesive. It forms a cured film by forming high-molecular bonds through photopolymerization. Examples of usable reactive oligomers include polyester resins, polyether resins, polyurethane resins, epoxy resins, polyacrylic resins, and silicone resins.

[0155] The reactive monomer acts as a crosslinking agent or diluent for the reactive oligomer, affecting the adhesive properties. Examples of the reactive monomer include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, and cyclic ethers.

[0156] The photopolymerization initiator absorbs light energy to generate free radicals or cations, thereby initiating photopolymerization. A suitable photopolymerization initiator can be selected and used according to the photopolymerizable resin.

[0157] The adhesive may be any adhesive developed in the past or in the future. In one or more embodiments, an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinyl pyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. may be used. The adhesive is not particularly limited as long as it has adhesive strength and viscoelasticity. However, from the perspective of ease of availability, an acrylic adhesive is preferably used. For example, the adhesive may contain a (meth)acrylate copolymer, a crosslinking agent, a solvent, etc.

[0158] The crosslinking agent may be a conventional or later developed crosslinking agent, and may include, for example, polyisocyanate compounds, epoxy resins, melamine resins, urea resins, dialdehydes, methylol polymers, and preferably polyisocyanate compounds.

[0159] The solvent may include common solvents used in the field of resin compositions, for example, alcohol compounds such as methanol, ethanol, isopropyl alcohol, butanol, and propylene glycol methoxy alcohol; ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, and dipropyl ketone; acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate; cellosolve compounds such as methyl cellosolve, ethyl cellosolve, and propyl cellosolve; and hydrocarbon compounds such as hexane, heptane, benzene, toluene, and xylene. These solvents may be used alone or in combination of two or more.

[0160] The thickness of the adhesive / bonding layer 130 can be appropriately determined based on the type of resin serving as the adhesive / bonding agent, the adhesive / bonding strength, the environment in which the adhesive / bonding agent is used, etc. In one embodiment, to ensure sufficient adhesive / bonding strength and minimize the thickness of the optical laminate, the thickness of the adhesive / bonding layer can be 0.01 to 50 μm, preferably 0.05 to 20 μm, and more preferably 0.1 to 10 μm.

[0161] The ultraviolet absorbing layer is not particularly limited as long as it is used to prevent degradation of the optical laminate due to ultraviolet rays. For example, salicylic acid ultraviolet absorbers (phenyl salicylate, p-tert-butyl salicylate, etc.), benzophenone ultraviolet absorbers (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), benzotriazole ultraviolet absorbers (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, etc.) can be used. -3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'- Hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(straight and side chain dodecyl)-4-methylphenol, octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy -5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, etc.), cyanoacrylate-based UV absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, etc.), triazine-based UV absorbers, etc., preferably benzotriazole-based UV absorbers or triazine-based UV absorbers that have high transparency and excellent effect of preventing degradation of polarizing plates or layers, and particularly preferably benzotriazole-based UV absorbers that have a more suitable spectral absorption spectrum. The above-mentioned benzotriazole-based ultraviolet absorber can also be a bis (Bis) substance, for example, it can be 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2,4,4-trimethylpentane-2-yl)phenol), 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2-hydroxyethyl)phenol), etc.

[0162] The hard coat layer is not particularly limited as long as it is used to protect members such as polarizing plates and layers from external physical and chemical impacts, and any hard coat layer previously developed or developed in the future can be used.

[0163] In one embodiment, the hard coat layer can be formed by applying a hard coat layer-forming composition to another member and then curing the composition using light or heat. The hard coat layer-forming composition is not particularly limited and may include, for example, a photocurable compound and a photoinitiator.

[0164] The above-mentioned photocurable compounds and photoinitiators can use substances generally used in the field without limitation. For example, the above-mentioned photocurable compounds can be photopolymerizable monomers, photopolymerizable oligomers, etc., for example, monofunctional and / or multifunctional (meth)acrylates can be mentioned, and the photoinitiators can be oxime esters, etc.

[0165] <Method for Manufacturing an Optical Laminated Body>

[0166] The present invention includes the method for producing the optical layered body described above. The method for producing the optical layered body is not particularly limited, and the optical layered body can be produced using any appropriate technique or the above-mentioned photolithography technique.

[0167] For example, the conductive layer in the above-mentioned polarizing plate can be formed by coating a functional conductive layer-forming composition on a triacetyl cellulose film or a cycloolefin polymer (COP) and then laminating it to a polyvinyl alcohol-based polarizer. It can also be formed by selectively coating the functional conductive layer composition on the triacetyl cellulose film or cycloolefin film surface of a polarizing plate prepared by laminating a triacetyl cellulose film or a triacetyl cellulose film and a cycloolefin film on both sides of a polyvinyl alcohol-based polarizer (23 μm, KURARAY) using an adhesive.

[0168] <Smart Window>

[0169] In addition to the optical laminate, the present invention also includes a smart window comprising the optical laminate. Furthermore, the present invention includes an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof, and an interior partition, and a building window comprising the smart window.

[0170] Reference Figure 5The car including the smart window of the present invention can be made by bonding vehicle glass 141 on both sides of an optical laminate including a liquid crystal layer 120 and an optical functional layer 110 using an adhesive / bonding layer 130. For example, it can be manufactured by placing an adhesive film and vehicle glass on both sides of the optical laminate, and then heating them at a temperature of 90°C and about 1 bar or in a vacuum state for 10 to 20 minutes using a press machine. It can also be manufactured by coating a resin on one side of the vehicle glass, vacuum bonding the vehicle glass on both sides of the optical laminate, and then UV curing. The above-mentioned adhesive film may include EVA (ethylene vinyl acetate) film, PVB (polyvinyl butyral) film, etc., and the above-mentioned resin may include a storage modulus (G') of 10 3 to 10 5 Pa's OCR resin, etc.

[0171] In addition, one or both sides of the optical layered body (see Figure 6 ) is attached to a building window (window glass) 142, or a window glass is attached to one side of the optical laminate in a laminating manner to manufacture a smart window product for a window, or a UV adhesive is applied to both sides of the optical laminate and then attached to the window glass, and then UV curing is performed to manufacture a smart window product for a window. Figure 6 Smart window products for windows with the same structure.

[0172] Implementation Method

[0173] The present invention will be described in more detail below based on examples. However, the embodiments of the present invention disclosed below are merely illustrative, and the scope of the present invention is not limited by these embodiments. The scope of the present invention is indicated in the claims, and all modifications within the meaning and scope of the claims are also included. In addition, "%" and "parts" indicating content in the following examples and comparative examples are by weight unless otherwise specified.

[0174] <Manufacturing Example>

[0175] Manufacturing Example 1: Manufacturing of a functional conductive layer composition

[0176] Poly(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS, Clevios TM A functional conductive layer composition was prepared by mixing 0.6 wt % of ethanol (Heraeus), 32.5 wt % of ethanol, 40 wt % of deionized water and 27 wt % of 2-methoxyethanol.

[0177] Manufacturing Example 2: Manufacturing of Polarizing Plate

[0178] A polarizing plate was prepared by bonding triacetyl cellulose films (40 to 60 μm TAC, manufactured by Konica) to both surfaces of a polyvinyl alcohol-based polarizer (23 μm, Kuraray) using an adhesive.

[0179] The conductive layer in the polarizing plate is formed by coating a triacetylcellulose film with a composition for forming a functional conductive layer and then laminating the film to a polyvinyl alcohol-based polarizer. During the coating process, the conductive layer is dried at 90°C for approximately 10 minutes to form a 3 μm thick functional conductive layer. This produces an optically functional layer comprising a functional conductive layer formed of a conductive polymer on one side of the polarizing plate.

[0180] <Examples and Comparative Examples: Production of Optical Laminated Body>

[0181] Examples 1 to 3

[0182] On a polyethylene terephthalate (PET, XG7PH8, Toray) substrate film having a thickness of 50 μm, the composition for forming a functional conductive layer of the above-mentioned manufacturing example 1 was applied to both sides of the substrate layer in such a manner that the thickness reached 3.0 μm after curing at 90°C for 10 minutes, and then dried at 90°C for 10 minutes in an oven (PR-4J, ESPEC) to form a first optically functional layer.

[0183] The composition for forming a functional conductive layer was applied to one or both sides of the substrate layer in the same manner as the first optically functional layer, except that the composition had a thickness of 1.0 μm or 3.0 μm after curing at 90°C for 10 minutes. Specifically, the thickness of the second optically functional layer and whether it was applied to both sides or one side were determined according to the information in Table 1. The composition was then dried in an oven (PR-4J, Espec) at 90°C for 10 minutes to form the second optically functional layer. Liquid crystal and polymer-dispersed liquid crystal were injected between the first optically functional layer comprising the functional conductive layer applied to the substrate and the second optically functional layer to produce the optical laminates of Examples 1 to 3, respectively.

[0184] Examples 4 to 6

[0185] The functional conductive layer composition of the above-mentioned manufacturing example 1 was applied to both sides of a polarizing plate manufactured according to the above-mentioned manufacturing example 2 as a substrate film in such a manner that the thickness after curing reached 3.0 μm, and then dried in an oven (PR-4J, Espec) at 90° C. for 10 minutes to form a first optical functional layer.

[0186] The optical functional layer is formed in the same manner as the above-mentioned first optical functional layer, but the composition for forming a functional conductive layer is applied to one side or both sides in such a manner that the thickness reaches 1.0 μm or 3.0 μm after curing at 90°C for 10 minutes, and dried in an oven (PR-4J, Espec) at 90°C for 10 minutes to form an optical functional layer. Liquid crystal and polymer-dispersed liquid crystal are injected between the optical functional layers coated on the substrate to produce the optical laminates of Examples 4 to 6, respectively.

[0187] The following describes a method for forming a functional conductive layer on a polarizing plate in more detail. The functional conductive layer composition of Manufacturing Example 1 is applied to one or both sides of a protective film 320 attached to protect the polarizer of the polarizing plate to a thickness of 1.0 μm or 3.0 μm after curing. The polarizer is then bonded to the polarizer using an adhesive or pressure-sensitive adhesive to form a polarizing plate substrate layer.

[0188] In each embodiment, the composition of the substrate layer, the thickness of the second optically functional layer, and whether the coating is applied to both sides or one side are respectively shown in Table 2 below.

[0189] [Table 1]

[0190]

[0191] [Table 2]

[0192]

[0193] Comparative Examples 1 and 2

[0194] Optical layered bodies of Comparative Examples 1 and 2 were prepared in the same manner as in Example 1, except that the functional conductive layer composition of Production Example 1 was replaced by the heat-shielding films including the metal reflective layer shown in Table 2 below.

[0195] [Table 3]

[0196]

[0197] -Ag film: Silver AG LOW-E film, Solar Gard

[0198] -Metallic film: ZV90-35 thermal insulation film, Zivent

[0199] <Experimental Example>

[0200] (1) Visible light reflectance evaluation

[0201] For the optical layered bodies of the above-mentioned embodiments and comparative examples, the visible light reflectivity can be measured and evaluated using one or more of the group consisting of KS L2016:2014, FT-IR, spectrophotometer, Nicolet, 6700, USA and UV-VIS-NIR, spectrophotometer, Perkin-Elmer, Lambda 950 and 1050, USA equipment. In the experimental examples of the present invention, the optical properties test method KS L2016:2014, 6.3 Optical properties test, JIS A 5759:2016, 6 test method, KS L 2514:2011, 4 spectral transmittance and spectral reflectivity are used. The results are shown in Tables 1 to 3 above.

[0202] (2) Evaluation of solar energy transmittance and rejection

[0203] For the optical laminates of the above-mentioned embodiments and comparative examples, the solar energy transmittance and the solar energy infrared blocking rate can be measured and evaluated using one or more of the group consisting of KS L 2016:2014, FT-IR, spectrophotometer (Spectrophotometer), Nicol, 6700, USA and UV-VIS-NIR, spectrophotometer (Spectrophotometer), PerkinElmer, Lambda 950 and 1050, USA equipment. In the experimental examples of the present invention, the optical properties test method KS L2016:2014, 6.3 Optical properties test, JIS A 5759:2016, 6 test method, KS L2514:2011, 4 spectral transmittance and spectral reflectance are used. The results are shown in Tables 1 to 3 above.

[0204] (3) Crack density and surface resistance evaluation

[0205] Regarding the functional conductive layers included in the above-mentioned embodiments and comparative examples, the crack density and the surface resistance increase rate were calculated according to Formulas 1 and 2 for the tensile deformation rates in the transverse direction (TD) of 0%, 1%, 2% and 10%, respectively, and the results are shown in Tables 1 to 3 above.

[0206] On the other hand, the crack density and the sheet resistance increase rate described in Tables 1 to 3 are larger values ​​among the measured values ​​of the first functional conductive layer and the second functional conductive layer.

[0207] The experimental data in Tables 1 to 3 above confirm that Examples 1 to 6, in which the optically functional layer includes a conductive polymer, exhibit solar energy rejection rates exceeding 60% and visible light reflectances below 10%, demonstrating superior thermal insulation performance and low reflectivity compared to the comparative examples. Furthermore, compared to the case where the optically functional layer is formed on only one side of the substrate layer (see Example 1), the thermal insulation rate is higher and the visible light reflectance is lower. Even with the same overall thickness, the crack density and the rate of increase in sheet resistance due to cracks are also lower, making the case where the optically functional layer is formed on both sides of the substrate layer (see Example 3) the most superior configuration.

[0208] Therefore, the optical layered bodies of Examples of the present invention can have higher performance in terms of conductive polymer materials than the structures containing metal materials in the functional conductive layers of Comparative Examples 1 and 2, and can also be confirmed to have excellent crack density relative to tensile strain.

[0209] Industrial applicability

[0210] According to the optical layered body of the present invention, since the transmittance of solar light is reduced and the infrared ray blocking rate is improved, energy efficiency can be improved.

Claims

1. An optical laminate comprising: liquid crystal layer; a first optical functional layer formed on one side of the liquid crystal layer; and a second optical functional layer formed on the other side of the liquid crystal layer and opposite to the first optical functional layer; The first optically functional layer and the second optically functional layer each independently comprise a substrate layer and a functional conductive layer, At least one of the first optically functional layer and the second optically functional layer includes two or more functional conductive layers.

2. The optical layered body according to claim 1, wherein The functional conductive layer includes a conductive polymer.

3. The optical laminate according to claim 2, wherein the conductive polymer comprises a polymer selected from the group consisting of polythiophene, poly(3,4-ethylenedioxythiophene), polyaniline, polyacetylene, polydiacetylene, polyphenylene, polyphenylene vinylene, polyphenylene sulfide, polythiophene acetylene, polythiophene vinylene, polyfluorene, polypyrrole, poly(3,4-ethylenedioxythiophene), poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, poly(3,4-ethylenedioxythiophene):camphor sulfonic acid, poly One or more of the group consisting of (3,4-ethylenedioxythiophene):toluenesulfonic acid, poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid, polyaniline:polystyrenesulfonate, polyaniline:camphorsulfonic acid, polypyrrole:polystyrenesulfonate, polypyrrole:camphorsulfonic acid, polypyrrole:toluenesulfonic acid, polypyrrole:dodecylbenzenesulfonic acid, polythiophene:polystyrenesulfonate, polythiophene:camphorsulfonic acid, polythiophene:toluenesulfonic acid and polythiophene:dodecylbenzenesulfonic acid. The optical layered body according to claim 2 , wherein the functional conductive layer has a thickness of 1.0 to 3.0 μm or less. 5 . The optical layered body according to claim 1 , wherein the substrate layer comprises at least one selected from the group consisting of cycloolefin resins, cellulose resins, acrylic resins, polyester resins, and polycarbonate resins. The optical layered body according to claim 1 , wherein the base layer includes a polarizer.

7. The optical layered body according to claim 1, wherein The liquid crystal layer is a polarizing film-liquid crystal POL-LC or a polymer dispersed liquid crystal PDLC. The optical layered body according to claim 1 , wherein the solar energy blocking rate of the optical layered body measured according to the optical performance test method KS L2016:2014, 6.3 is 60% or more.

9. The optical laminate according to claim 1, wherein at a tensile deformation rate of greater than 1% and less than 10%, at least one of the crack density values ​​of the functional conductive layer calculated according to the following formula 1 is 0 to 0.05: [Formula 1] ρ(ε)=l(ε) / A In the formula 1, ε represents the tensile deformation rate (%), A represents the area of ​​the observation area (mm 2 ), ρ(ε) represents the crack density value of the functional conductive layer calculated under the tensile deformation rate ε, and l(ε) represents the crack area (mm2) of the functional conductive layer in the observation area A measured under the tensile deformation rate ε. 2 ). 10 . The optical layered body according to claim 9 , wherein when ε in Formula 1 is 2%, the crack density of the functional conductive layer calculated according to Formula 1 is 0.

11. The optical layered body according to claim 1, wherein at a tensile deformation rate of 1% to 10%, at least one of the increase rates of the surface resistance of the functional conductive layer calculated according to the following formula 2 is 15% or less: [Formula 2] δ(ε)=[{RS(ε) / RS(0)}-1]*100 In Formula 2, δ(ε) represents the surface resistance increase rate (%) of the functional conductive layer calculated under the tensile deformation rate ε, RS(ε) represents the surface resistance value (Ω / □) of the functional conductive layer measured under the tensile deformation rate ε, RS(0) represents the surface resistance value (Ω / □) of the functional conductive layer measured in the initial state with the tensile deformation rate of 0%, and ε has the same meaning as in Formula 1. 12 . The optical layered body according to claim 11 , wherein at a tensile deformation rate of 1% to 10%, at least one of the increase rates of the surface resistance of the functional conductive layer calculated according to Formula 2 is 14% or less. 13 . The optical layered body according to claim 1 , wherein the functional conductive layer and the substrate layer are directly in contact with each other without a separate substrate being interposed therebetween. The optical layered body according to claim 1 , wherein the functional conductive layer and the base material layer are directly in contact with each other with an easy-adhesion layer interposed therebetween. 15 . The optical layered body according to claim 1 , wherein the liquid crystal layer comprises at least one selected from the group consisting of spherical spacers and columnar spacers. 16 . The optical layered body according to claim 1 , further comprising at least one selected from the group consisting of a protective film, a sticking / adhesive layer, a UV absorbing layer, and a hard coat layer. 17 . A method for producing the optical layered body according to claim 1 . 18 . A smart window comprising the optical laminate according to claim 1 .

19. An automobile, wherein the smart window according to claim 18 is applied to at least one of a front window, a rear window, a side window, a skylight, and an interior partition.

20. A window for a building, comprising the smart window according to claim 18.

Citation Information

Patent Citations

  • Light control film

    JP2018010035A